2003
DOI: 10.1016/s0926-3373(02)00218-7
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR spectroscopic investigation of the reactivity of NOx species adsorbed on Cu2+/ZrO2 and CuSO4/ZrO2 catalysts toward decane

Abstract: The nature of the NO x species produced on NO adsorption and its co-adsorption with O 2 at room temperature on zirconia-supported copper(II) catalysts has been studied by means of in situ FT-IR spectroscopy. The samples were prepared by impregnation of zirconia with aqueous solutions of copper(II) nitrate and sulfate. The structural identification of the surface NO x complexes exhibiting absorptions in the fundamental nitro-nitrato region was performed by analyzing the combination bands of the nitrate species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 49 publications
4
28
0
Order By: Relevance
“…The intensities of these bands do not change synchronously with the increase in the temperature. Therefore, they are assigned to the m as (NO 2 ) modes of two types of inorganic bidentate nitrito species [20,42]. It should be pointed out that no adsorbed NO x compounds have been detected during the high-temperature adsorption of NO on the WZ sample [20] which confirms that the species associated with the bands at 1250 and 1220 cm )1 originate from the thermal transformation of the cismethyl nitrite.…”
Section: Adsorption Of Nitromethanementioning
confidence: 68%
See 1 more Smart Citation
“…The intensities of these bands do not change synchronously with the increase in the temperature. Therefore, they are assigned to the m as (NO 2 ) modes of two types of inorganic bidentate nitrito species [20,42]. It should be pointed out that no adsorbed NO x compounds have been detected during the high-temperature adsorption of NO on the WZ sample [20] which confirms that the species associated with the bands at 1250 and 1220 cm )1 originate from the thermal transformation of the cismethyl nitrite.…”
Section: Adsorption Of Nitromethanementioning
confidence: 68%
“…A broad, unresolved absorption develops, which appears with maxima at 1255 and 1227 cm )1 at 250°C. In analogy with the WZ sample, these two bands are assigned to the m as (NO) 2 modes of two types of inorganic bidentate nitrito species [20,42]. At 300°C the adsorbed NO and cis-CH 3 ONO disappear from the spectrum which is accompanied by decrease in the intensities of the formate bands.…”
Section: Adsorption Of Nitromethanementioning
confidence: 99%
“…4a. The spectral region between 1700 and 1200 cm −1 is characteristic for the nitrate and nitrite species coordinated on TiO 2 and ZrO 2 [28][29][30]. The observed frequencies at 1644 and 1209 cm −1 can be attributed to bridging nitrates, while the features at 1578, 1550 and 1280 cm −1 can be assigned to bidentate nitrates [8,31].…”
Section: Structural Characterization Of the Synthesized Materialsmentioning
confidence: 94%
“…The results of our previous investigation [7] have shown that the presence of sulfate ions in zirconia-supported copper(II) catalysts strongly modifies the reactivity of adsorbed NO x species toward saturated long-chain hydrocarbon (decane). The aim of this paper is to investigate the effect of sulfate ions in zirconia-supported cobalt catalysts on the reactivity of adsorbed NO x species toward methane.…”
Section: Introductionmentioning
confidence: 95%
“…In general, the mechanism of selective catalytic reduction of nitrogen oxides in excess oxygen on various oxide catalysts involves the interaction of strongly adsorbed NO x − species (x is 2 or 3) with the hydrocarbon [3][4][5][6][7][8][9]. The results of our previous investigation [7] have shown that the presence of sulfate ions in zirconia-supported copper(II) catalysts strongly modifies the reactivity of adsorbed NO x species toward saturated long-chain hydrocarbon (decane).…”
Section: Introductionmentioning
confidence: 99%